Pemetaan Tingkat Kebisingan pada Fabrikasi Bollard Proyek BMPP 60 MW di Bengkel Konstruksi Plat 2 - Restu Hikmah Ayu Murti; Adika Pratama (Prosiding ESEC, 2023)
High noise levels resulting from the fabrication process of the BMPP 60 MW bollard projectrequire control measures to reduce noise intensity and ensure that all workers are not exposed to work-related health issues due to noise exposure effects. The aim of this study is to measure the noise levels generated by activities in construction workshop plat 2 and conduct noise mapping. The research method employed is noise mapping using Surfer 16 software to create noise contours. Noise measurements were taken at 52 points within construction workshop plat 2 using a multifunction environment meter 5 in 1, and the allowed work time was calculated based on the NIOSH method. The research results indicate that at points 29, 30, 31, 32, 45, 46, 47, 48 located in the grinding and welding area, the noise level exceeds 85 dB. Therefore, if no control measures are implemented, based on the calculated ideal working times for each point in sequence, they are 6.1 hours, 5.7 hours, 5.4 hours, 5.5 hours, 6.6 hours, 6.8 hours, 6.2 hours, and 6.5 hours, respectively. The conclusion of this study is that out of the 8 points exceeding 85 dB according to the Threshold Limit Value (TLV) based on the Kemenaker Number 5 of 2018 so that control is needed in the form of installing noise safety signs and use of earplugs.